Effect of Independent Curriculum Implementation on Multiple Intelligences and Pancasila Character in Grade IV - Triutami, Dwinisari; Sulistyorini, Dwi (Universitas Pakuan, 2025)
This study aims to analyze the effect of the implementation of the Independent Curriculum on the development of multiple intelligences and the character profile of Pancasila Students in grade IV students of Padangan 1 Elementary School, Kayenkidul District, Kediri Regency. The method used in this study is quantitative, with data collection through a questionnaire instrument distributed to 25 students, as well as interviews with teachers involved in the learning process. The data obtained were then analyzed to determine the impact of the implementation of the Independent Curriculum based on multiple intelligences. The results showed that 72% of students were included in the interactive domain category which includes interpersonal and kinesthetic intelligence. After the implementation of learning adapted to multiple intelligences, there was an increase in the average student learning score of 12% between the pre-test and post-test. These findings support that the implementation of the Independent Curriculum not only improves learning outcomes, but also contributes to the development of student character in accordance with the Pancasila Student Profile, such as collaboration and tolerance. This study emphasizes the importance of a multiple intelligence-based approach in education to prepare students to face challenges in the era of globalization and invites educators to consider implementing a curriculum that can improve the quality of learning and student character holistically.